Language as exile and home in relations of alterity: an approach to two novels by J.M Coetzee (2017)
In contemporary literature, the works of the South African writer John Maxwell Coetzee provide an important fictional universe for the understanding of colonialism, as well as the wars and exiles associated with it. This paper seeks to problematize and understand the place occupied by language in the relation ships of otherness created in the midst of conflict, oppression and isolation, in the novels Foe (1986) and Age of Iron (1990). Through the characters in these novels we will explore the possibilities and impossibilities of language as a cultural configuration determined by social circumstances. Finally, the perception of the face of the other, language as a dwelling place or as a grammar of inhumanity, are some of the metaphors that will be used in the creation of meaning with regard to the above stated themes